2022
DOI: 10.1155/2022/8315519
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Serum β-Human Chorionic Gonadotropin on Pregnancy Complications and Adverse Pregnancy Outcomes: A Systematic Review and Meta-Analysis

Abstract: Background. The relationship among elevated serum β-human chorionic gonadotropin (β-hCG), the incidence of pregnancy complications, and adverse pregnancy outcomes has been controversial. Differences in study design, subject bias due to demographic characteristics, and differences in local medical levels could contribute to inconsistent results. Methods. Literature searches were performed in PubMed, EMBASE, Medline, Central, China National Knowledge Infrastructure (CNKI), Wanfang, and China Science Digital Libr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 23 publications
0
0
1
Order By: Relevance
“…According to some data βHCG values above 4.0 MoM were associated with low birth weight and hypertensive disorders in 22.5% of pregnant women. βHCG values, over 10 MoM were found in 92% of cases with adverse perinatal outcomes in terms of severe fetal growth restriction and neonatal complications, placental abruption as well as severe hypertensive disorders [19]. Authors reported an association of elevated second-trimester HCG values with growth restriction, which we did not establish [20].…”
Section: Discussioncontrasting
confidence: 59%
“…According to some data βHCG values above 4.0 MoM were associated with low birth weight and hypertensive disorders in 22.5% of pregnant women. βHCG values, over 10 MoM were found in 92% of cases with adverse perinatal outcomes in terms of severe fetal growth restriction and neonatal complications, placental abruption as well as severe hypertensive disorders [19]. Authors reported an association of elevated second-trimester HCG values with growth restriction, which we did not establish [20].…”
Section: Discussioncontrasting
confidence: 59%